TURISMO SUSTENTÁVEL: ANÁLISE DA PERCEPÇÃO DA GESTÃO AMBIENTAL NO MUNICÍPIO DE COXIM – MS. - Martins, Luciana; Martins, Lucilene; Miranda, Bianca; Andrade, Camila; Ferreira, Patrícia (ANAIS DO ENIC, 2018)
-